Evolução da acessibilidade na web: um levantamento da implementação de requisitos de acessibilidade em aplicações web - Krepsky, Allan Aslley (2015)
The Web community has struggled more and more to allow the access for digital information to people with disabilities. However, the correct implementation of technologies that promote accessibility requires that Web developers have the knowledge of a serie of guidelines and specifications elaborated by the W3C (World Wide Web Consortium). This information, together with the Web Accessibility culture, encounter as an obstacle the lack of interest from developers on the subject. This fact is compounded when taken into account the rich Internet applications, RIAs (Rich Internet Applications), which enable user interaction with the interface. In order to assist the implementation of accessible Web content in RIAs, the WAI (Web Accessibility Initiative) elaborated the specification ARIA (Accessible Rich Internet Applications). This study has the objective of investigating the evolution of the Web accessibility, according to the ARIA specification. To this end, a script was developed to monitor the evolution of the use of some elements and attributes HTML (HyperText Markup Language), according to the ARIA specifications and WCAG 2.0 (Web Content Accessibility Guidelines). The script was executed to monitor a sample websites for a certain period of time. According to the data obtained, it was observed that, despite the availability of ARIA and WCAG 2.0 documents, there were small improvements in accessibility requirements in Web applications.